2006
DOI: 10.1007/s11064-006-9086-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemic Neuronal Insults on Amyloid Precursor Protein Processing

Abstract: The nature of the association between ischemic stroke and Alzheimer's disease (AD) at the cellular and molecular level is still unknown. We evaluated the effect of ischemic neuronal insults on the regulation of amyloid precursor protein (APP) processing. We used an in vitro model of cerebral ischemia (oxygen-glucose deprivation) to evaluate the effect of ischemic neuronal insults on the amyloidogenic and non-amyloidogenic pathways using human neuroblastoma cell line and primary cultured cells of transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
(26 reference statements)
1
21
1
1
Order By: Relevance
“…Wen et al (40) found that both activity and expression of BACE1 were significantly increased in rats under transient cerebral ischemia. Another study, however, using AD transgenic mice overexpressing mutant APP showed that neither expression nor activity of BACE was significantly affected by ischemic insult; instead ADAM10 was markedly increased in the early stage of ischemic insult and then down-regulated at later stages (41). Other studies report a drastic decrease in ADAM10 and TACE protein levels with unchanged BACE1 levels in human neuroblastoma SH-SY5Y cells subjected to chronic hypoxic treatments (42)(43)(44).…”
Section: Discussionmentioning
confidence: 98%
“…Wen et al (40) found that both activity and expression of BACE1 were significantly increased in rats under transient cerebral ischemia. Another study, however, using AD transgenic mice overexpressing mutant APP showed that neither expression nor activity of BACE was significantly affected by ischemic insult; instead ADAM10 was markedly increased in the early stage of ischemic insult and then down-regulated at later stages (41). Other studies report a drastic decrease in ADAM10 and TACE protein levels with unchanged BACE1 levels in human neuroblastoma SH-SY5Y cells subjected to chronic hypoxic treatments (42)(43)(44).…”
Section: Discussionmentioning
confidence: 98%
“…In the latter conditions, various factors such as oxidative stress (10,48,49), hypoxia (50,51), and ischemia (52) have been proposed as causes of BACE1 up-regulation, and different underlying mechanisms have been described, including the activation of hypoxia-inducible factor 1 (53), the decrease of GGA3 activity (30), and the loss of micro RNA specific clusters (32).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Although the underlying mechanism remains unclear, positron emission tomography scans show that patients exhibit cerebral hypometabolism many years before being diagnosed with AD. 7,8 Work in rodent models of AD indicates that severe ischemic insults, such as middle cerebral artery occlusion, increase both A␤ 9 -11 and phosphotau levels.…”
mentioning
confidence: 99%